Knowledge about birth preparedness and complication readiness and associated factors among primigravida women in Addis Ababa governmental health facilities, Addis Ababa, Ethiopia, 2015 - Ayelech Kidanemariam Mulugeta; Berhanu Wordofa Giru; Balcha Berhanu; Tefera Mulugeta Demelew (BMC, 2020)
Abstract Background Globally, every minute, at least one woman dies from complications related to pregnancy or childbirth. The situation is more serious for women in Sub-Saharan Africa which also include Ethiopia. Birth preparedness is a strategy to promote the timely use of skilled maternal and neonatal care, especially during childbirth. Based on the theory, preparing for childbirth reduces delays in obtaining this care. In adequate preparation for rapid action in the event of obstetric complications are well documented factors contributing to delay in receiving skilled obstetric care. Hence, the aim of this study was to assess the knowledge of birth preparedness and complication readiness and its associated factors among primigravida in Addis Ababa Governmental Health Facilities. Methods A quantitative facility based cross-sectional study design and client exit interview questionnaire were used. Simple random and census sampling was used to select the health care facilities and study participants, accordingly. The data were entered using Epidata version3.1 and analysed by window statistical package for social science version 20 software. Logistic regression model was used to assess the knowledge by predictor's variables. Result From 442 respondents the response rate was 422 (95.5%). Based on finding, the respondents were knowledgeable on danger signs in pregnancy, labour, postnatal and new born neonate 113(26.8%), 47(11.1%), 60(14.2%) and 46(10.9%), respectively. According to birth preparedness, 64 (15.2%) of primigravida women were knowledgeable. In this study, factors associated with knowledge of birth preparedness and complication readiness were found to be being married [AOR = 0.110, 95%CI (0.026, 0.461);], house hold monthly income of 1000-3000 [AOR = 3.362(1.203,9.393);], knowledgeable for key danger signs of labour with [AOR = 3.685, 95%CI (1.157, 11.737);] and knowledgeable for key danger signs of post-partum period with [AOR =5.117, 95%CI (1.388, 18.863);]. Conclusion The knowledge of primigravida women for birth preparedness and its complication readiness was low. Information given about danger sign and birth preparedness during ANC follow up was not comprehensive. Therefore, family health care providers, health facility, other partners, program level managers and policy makers take their responsibility and work together to improve the health education service and increase knowledge on birth preparedness and complication readiness through easily accessible health education strategies.